Isiac Cults, Civic Priesthood and Social Elite in Hellenistic Demetrias (Thessaly): Notes on RICIS 112/0703 and beyond - Kravaritou, Sofia (Tekmeria, 2016)
In 2nd cent. BC, following the decline of the Macedonian power and the abandonment of the baseilion of Demetrias by its royal masters, there were many significant sociopolitical changes that took place in the region, such as the arrival of the Romans, the reorganization of local communities after the creation of the Magnesian Koinon, as well as the reconstruction of the civic and sacred space of Demetrias. Also, royal euergetism towards the city and its public affairs was eventually replaced by the benefactions pursued by benevolent wealthy individuals and prominent members of the local elite. The paper aims to shed light on the sociopolitical strategies, which emerged within this new model of civic-based euergetism that was related primarily to local cult matters. In particular, the phenomenon will be discussed in relation to Isiac cults. I will seek to examine the ways Isiac cults and their devotees adapted and operated in the new political, civic and sacred space, as well as into the new social and cultural environment of the second century community of Demetrias.